Compensation for Damages Caused by Robot - Sara Mohamed Dager; Mothana Abdulkadem Mashaf (Periodica Journal, 2023)
Compensation for robot damage is considered the next stage for the establishment of civil liability for those damages, and that the injured person here, like any injured person, has the right to compensation, where compensation is considered a penalty or in exchange for damage.
Keywords: Robot; Compensation; Damages